Health concerns and attitudes towards research participation in a community of rural Black Americans. Issue 2 (15th March 2023) - Amofa, Priscilla A.; Kurasz, Andrea M.; Smith, Glenn E.; Levy, Shellie-Anne
ABSTRACT: Objectives: Describe health concerns of Black Americans as they age and what influences their participation in aging and clinical research. Methods: Fifty participants attended focus groups and completed questionnaires to identify barriers to research participation and attitudes toward dementia screening. Bivariate correlations explored associations between barriers to research participation and attitudes toward dementia screening. Results: Cancer, hereditary conditions, vascular conditions, memory disorders, and psychological disorders were the greatest health concerns. Time demands, mistrust, lack of knowledge about potential research, and stigma were identified as barriers for research participation. Incentives, better understanding of how proposed research will benefit the community, lifestyle modification studies, active presence of principal researchers/clinicians, and community investment were identified as factors to improve participation. Questionnaires revealed mistrust and religious beliefs to be among the primary barriers. Attitudes toward dementia screening reflected perceived stigma, suffering, and subsequent loss of independence. Higher barriers to participation were associated with perceived stigma and loss of independence related to dementia screening. Conclusions: Successfully recruiting Black Americans for aging and clinical research remains a challenge. This study identifies barriers to participation and offers suggestions for planning and recruitment.